ТЕЛЕМАТИЧНІ ТЕХНОЛОГІЇ ЯК ІНСТРУМЕНТ ПІДВИЩЕННЯ ЯКОСТІ ПІДГОТОВКИ ФАХІВЦІВ ТРАНСПОРТНОЇ ГАЛУЗІ - Борець, Олексій; Борець, Ірина (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2025)
An important task for higher education institutions preparing specialists in transportation management and logistics is to enhance the quality of educational services in the context of digitalization, European integration, and the globalization of the labor market. The implementation of modern educational technologies (EdTech) is becoming increasingly significant as they can ensure effective professional training and the competitiveness of graduates. The main goal of this research is to analyze the possibilities of integrating digital technologies into the training of transport sector specialists, identify the factors influencing the quality of the educational process, and develop recommendations to improve the effectiveness of educational services. Special attention is paid to the use of telecommunication tools, cloud platforms, and distance and blended learning systems for all forms of the educational process. The study employs a range of general scientific methods: analysis, synthesis, comparison, classification, abstraction, induction, and deduction. These methods allow for an in-depth study of existing educational technologies and learning models, assessing their effectiveness and identifying areas for improvement in the training of transport sector specialists in the context of digital transformation. As a result, it was found that the Ukrainian education system has significant potential due to its fundamental preparation, experience in working with international students, and accessibility. However, it requires updating teaching methods, actively implementing EdTech solutions, and modernizing the content of educational programs in line with international market requirements. The use of digital tools contributes to the enhancement of the educational process, the development of digital and management competencies. In conclusion, we suggest that the integration of modern educational technologies, including distance learning platforms, multimedia content, and online communication tools, is a key condition for forming highly qualified specialists who can navigate the dynamic environment of the transport sector. This requires the regular updating of educational programs and methodologies to meet labor market demands.